Estudo da influência da glicemia nas aferições do PET-CT com 18F-fluoro-deoxi-glicose (18F-FDG) em órgrãos normais. Análise de 5623 pacientes - Sprinz, Clarice (2021)
Our purpose was to evaluate the effect of glycemia on 18F-FDG uptake in normal organs of interest. The influences of other confounding factors, such as body mass index (BMI), diabetes, age, and sex, on the relationships between glycemia and organ-specific standardized uptake values (SUVs) were also investigated. We retrospectively identified 5623 consecutive patients who had undergone clinical PET/ CT for oncological indications. Patients were stratified into groups based on glucose levels, measured immediately before 18F-FDG injection. Differences in mean SUVmax values among glycemic ranges were clinically significant only when >10% variation was observed. The brain was the only organ that presented a significant inverse relationship between SUVmax and glycemia (p < 0.001), even after controlling for diabetic status. No such difference was observed for the liver or lung. After adjustment for sex, age, and BMI, the association of glycemia with SUVmax was significant for the brain and liver, but not for the lung. In conclusion, the brain was the only organ analyzed showing a clinically significant relationship to glycemia after adjustment for potentially confounding variables. The lung was least affected by the variables in our model, and may serve as an alternative background tissue to the liver.